Genetic signature and profiling of head and neck cancer: where do we stand?. Issue 2 (April 2017) - Paczkowska, Julia; Szyfter, Krzysztof; Giefing, Maciej; Wierzbicka, Malgorzata
Abstract : Purpose of review: To focus on two novel aspects of head and neck squamous cell carcinoma (HNSCC) genetics of special interest: the epithelial–mesenchymal transition (EMT) process, an initial step in tumor progression that finally leads to metastasis formation, by explaining how genes as well as epigenetic factors control this process, and the new diagnostic options based on the analysis of circulating tumor cells (CTCs) and cell-free DNA (cfDNA) that could revolutionize diagnosis in the coming years. Recent findings: We present an intriguing recently described group of factors, namely miRNAs, deregulated during EMT. MiRNAs could serve as novel markers of EMT and metastasis formation and are also a potential therapeutic target. Second, we show recent findings on CTC and cfDNA analysis in HNSCC that demonstrate the usefulness of this new diagnostic approach. Summary: We stress the importance of EMT in the context of metastasis formation and the potential of liquid biopsies in clinical practice.